Neutrophil Functional Heterogeneity: Identification of Competitive Phagocytosis - Hellebrekers, Pien; Hietbrink, Falco; Vrisekoop, Nienke; Leenen, Luke P. H.; Koenderman, Leo (Frontiers in Immunology, 2017)
Introduction – Phagocytosis by neutrophils is a key process in the innate immune response against invading micro-organisms. Despite reported heterogeneity in other neutrophils functions, little is known regarding differences in phagocytosis by individual cells. Therefore, we tested the hypothesis that heterogeneity is present in the neutrophil compartment in its potency to phagocytize bacteria. Methods – Phagocytosis assays were performed in suspension with isolated neutrophils and Staphylococcus aureus expressing different fluorescent proteins at MOI’s between 1 and 10. Repetitive addition of bacteria with different fluorescent proteins and MOI’s was used to compare the phagocytic capacity of S. aureus-GFP positive and negative neutrophils and exclude randomness. Results – The percentage and MFI of S. aureus-GFP positive neutrophils increased with higher MOI’s. The increase in MFI was due to phagocytosis of multiple bacteria per neutrophil as was confirmed by confocal imaging. Sequential phagocytosis of GFP- and mCherry expressing S. aureus showed a non-random process, as S. aureus-GFP positive neutrophils preferentially phagocytized S. aureus-mCherry. Conclusion – All neutrophils were able to phagocytize S. aureus, but some were much more potent than others. Therefore, at physiologically relevant MOI’s these potent phagocytizing neutrophils will outcompete the uptake of bacteria by less competent cells in a process we propose to name ‘competitive phagocytosis’. Keywords – Granulocyte, bacteria, Staphylococcus aureus, innate immunity, PMN